INFLUENCE OF ADVERTISING ON BOOK MARKET CUSTOMER - VAIŠVILIENĖ, ALINA (Knygotyra, 2010)
The increasing competition in the book market provides the basis for the relevance of research in the field of book advertising: advertising affects the customer’s perception and attitude, provokes interest in an advertised book or induces to buy it; on the other hand, employment of advertising in smaller sectors of business is related to a greater risk. The object of the study was the influence of advertising on customer in the book market. The scientific-practical problem was the ways of systematising and evaluating the influence of advertising on book business. The polysemantic, wide and unspecified environment of influence, interdisciplinary character, and abundance of evaluation criteria complicate the solution of this problem. The modes of influence of advertising on the book market are distinguished and the factors determining this influence are discussed to analyse the way an individual is influenced by advertising and what differences are crucial among several ways of experiencing the same phenomenon. Analysis of different modes of advertising and experiencing advertising incapacitates a better understanding of the potential of the influence of book advertising. Several phenomenographic techniques were employed to analyse data collected via unstructured interview. The unstructured interview method was used to identify the ways advertising affects the customer; the method was employed to analyse the experience, views, attitudes of customers, related to the choice of books, estimation and reading, the role advertising plays in choosing a book, the factors that shape the attitude of a reader towards a book and incite buying it. The differences in and the circumstances of the influence of advertising, as well as the factors differentiating the influence were clarified in the course of study. The research could be useful for book publishing and saling enterprises as well as for marketing specialists of the mentioned area in planning and implementing book advertising campaigns and in seeking to manage more efficiently the flows of information and communication. The research gives an insight into the potential of book advertising in the market framework, helps in making a right choice and controlling the mode of influence.